1999
DOI: 10.1056/nejm199912163412502
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy with Efavirenz, Nelfinavir, and Nucleoside Reverse-Transcriptase Inhibitors in Children Infected with Human Immunodeficiency Virus Type 1

Abstract: In HIV-1-infected children who were previously treated with nucleoside reverse-transcriptase inhibitors, the combination of efavirenz, nelfinavir, and nucleoside reverse-transcriptase inhibitors was generally well tolerated and had a potent and sustained antiviral effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
135
3
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(149 citation statements)
references
References 19 publications
10
135
3
1
Order By: Relevance
“…4,5 Diarrhea was reported for 18% of participants in a trial of a nelfinavir-based regimen. 6 In our study, approximately one fourth of all children experienced very mild or greater nausea/vomiting/abdominal pain, loss of appetite, and/or diarrhea. Although PI therapy was associated with greater gastrointestinal symptoms, only diarrhea differed significantly between treatment groups.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…4,5 Diarrhea was reported for 18% of participants in a trial of a nelfinavir-based regimen. 6 In our study, approximately one fourth of all children experienced very mild or greater nausea/vomiting/abdominal pain, loss of appetite, and/or diarrhea. Although PI therapy was associated with greater gastrointestinal symptoms, only diarrhea differed significantly between treatment groups.…”
Section: Discussionmentioning
confidence: 49%
“…1,2 Clinical trials have demonstrated the effectiveness of PI combination therapy (PI therapy) in decreasing plasma HIV RNA levels, although the proportion of children with virologic suppression to undetectable levels is generally smaller than the corresponding proportion of adults. [3][4][5][6] Antiretroviral regimens including PIs have been shown to increase CD4 ϩ cell counts, even for children with advanced disease, [4][5][6][7][8][9] and studies are now beginning to document their effects on clinical outcomes. Baseline and treatment-mediated changes in immunologic and virologic markers were independent predictors of survival in a meta-analysis of pediatric antiretroviral clinical trials, and virologic markers predicted weight growth and cognitive failure among children Ͼ1 year of age.…”
mentioning
confidence: 99%
“…Despite the widening scope of using ART (29), HIVinfected children still less frequently reach undetectable HIV-RNA viral load than adults (14)(15)(16). It is mandatory to enquire about the underlying reasons for such discrepancy and so far few studies have assessed the immunologic characteristics of pediatric patients, especially those who show a good response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Peak EFV plasma concentrations are reached 3 -5h after a single oral dose and become steady at 6 -7 days (Maggiolo, 2009). An important pharmacokinetic inter-individual variability has been reported in patients taking EFV: a daily dose of 600mg usually results in a C max of 12.9 ± 3.7M and a C min of 5.6 ± 3.2M (Starr, 1999;Staszewski, 1999), but higher levels (between 30 -50M) have been observed in as many as 20% of patients (Marzolini, 2001;Burguer, 2006). This drug is extensively biotransformed into inactive hydroxylated metabolites via the cytochrome P450 system, and CYP2B6 is likely to be the corresponding isoenzyme.…”
Section: Efavirenzmentioning
confidence: 99%